2011
DOI: 10.1002/pon.1924
|View full text |Cite
|
Sign up to set email alerts
|

No improvement in distress and quality of life following psychosocial cancer rehabilitation. A randomised trial

Abstract: A 6-day residential rehabilitation course did not relieve cancer patients' distress or improve their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
(48 reference statements)
0
17
1
1
Order By: Relevance
“…9 Spinal studies assessing QoL have used inter alia indices such as the Short Form (SF)-36, SF Health Survey-12 and Oswestry Disability Index (ODI). 1 -3,24 -28 Th ese studies have demonstrated signifi cant problems in multiple domains in patients awaiting spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9 Spinal studies assessing QoL have used inter alia indices such as the Short Form (SF)-36, SF Health Survey-12 and Oswestry Disability Index (ODI). 1 -3,24 -28 Th ese studies have demonstrated signifi cant problems in multiple domains in patients awaiting spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Die statistische Erfolgsevaluation, bezogen auf Lebensqualität, Angst und Depressivität, zeigte für die Unterskalen emotionale Rollenfunktion, Insomnie, Fatigue und Schmerz ein signifikant schlechteres Outcome für die Gruppenteilnehmer, bei allerdings geringer Stichprobengröße, so dass letztlich der Benefit für die Teilnehmer nicht abschließend beurteilt werden kann. Ähnliche Ergebnisse haben auch andere Autoren berichtet (Rottmann et al 2012;Ludwig et al2014). Betreffend die EORTC QLQ-C30-Unterskalen "Fatigue", "Übelkeit und Erbrechen" und "Schlafstörungen" wäre eine denkbare Erklärung, dass sich doch möglicherweise zufällig in der Interventionsgruppe einige objektive erkrankungsbezogene Parameter verschlechtert haben, die in dem Zusatzfragebogen zu Ereignissen seit t0 nicht erfasst wurden und die sich in diesen Unterskalen abbilden.…”
Section: Diskussionunclassified
“…Two small studies evaluated the impact of natural restorative environmental intervention on cognitive function in patients with breast cancer (Cimprich, 1993;Cimprich & Ronis, 2003). One study used a pre-and • Natural restorative environmental (Cimprich, 1993;Cimprich & Ronis, 2003) • Qigong (Oh et al, 2012) • Structured rehabilitation (Rottmann et al, 2012) • Vitamin E (Chan et al, 2004;Jatoi et al, 2005) • Pharmacologic approaches -Methylphenidate (Bruera et al, 1992;Butler et al, 2007;Escalante et al, 2014;Gagnon et al, 2005;Gehring et al, 2012;Gong et al, 2014;Lower et al, 2009;Mar Fan et al, 2008;Meyers et al, 1998;Schwartz et al, 2002 Both studies noted improvements in the capacity to direct attention for patients prior to adjuvant therapy. Further research is needed to explore its effect on cognitive function after cancer treatment.…”
Section: Databases: Cinahl ® Pubmed and Cochrane Collaborationmentioning
confidence: 99%
“…A total of 394 breast, prostate, and colon cancer survivors were randomly assigned to a six-day residential psychosocial rehabilitation program that included education, supportive discussions, physical activity, relaxation, massage, social activities, and dietary counseling or to a control group (Rottmann et al, 2012). Objective cognitive performance was not assessed and perceived cognitive function (a one-item measure) significantly improved in the control group when compared to those in the structured rehabilitation intervention group.…”
Section: Databases: Cinahl ® Pubmed and Cochrane Collaborationmentioning
confidence: 99%